EKONOMI INDONESIA, ISLAMIKAH? Economic Islamicity Index (EI2) Indonesia dalam Perspektif Maqashid Syariah - Sholihin, Muhammad (IAIN Tulungagung, 2020)
This article aims to measure how closely or Islamic the Indonesian economy is when analyzed with the theory of maqashid sharia. This goal is based on empirical facts that the Indonesian economy is based on Pancasila, which is in fact compatible with Islamic values. This is the primary fondation of the argument why research is important. To be able to obtain information related to the objectives of this research, this study applies an integrative approach, which is an approach that combines online survey methods and library approaches, or library research. Strengthening understanding and understanding of the data, this study uses the fiqh paradigm, specifically the sharia maqashid theory and the economic development paradigm, which specifically borrows the theory put forward by Abbas Mirakhor and Hossein Askari about the dimensions of Islamic development. The findings of this study are generally formulated into a thesis that Indonesia is now faced with the ambivalence of state religiosity and people's economic behavior: a negative relationship between state economic policy and people's economic behavior. When the state formulates economic policy it is trapped in neo-liberalism, and is far from Islamic principles.